E-Commerce Catalogue Application For EON (Edaran Otomobil Nasional) - Tan, Pei Ling (2001)

(untitled)
The purpose of this project is to develop a prototype e-commerce catalogue application for EON (Edaran Otomobil Nasional). The EON web page provides online customization and ordering of cars services to customers. The cars available are Proton Waja, Proton Perdana V6, Proton Wira Sedan and Proton Iswara. Other services include on-line booking of time to service cars, information about the cars such as prices, model specifications, pictures of cars etc, links to other homepages such as financial institution, insurance companies and second hand Proton cars dealers. There is also information about the EON sales branches and EON services centers throughout Malaysia. The business module of EON web page consiss of four main funtional modules. They are the view information module, online customization and ordering module, on-line booking module and advertisement module. This project uses the Web Page Development Methodology (WPD) as the development methodology. Finally, this project discusses some flaws, constraints and recommendations for future development.